Air stable NHCs: a study of stereoelectronics and metallorganic catalytic activity. Issue 1 (15th October 2014) - Furfari, Samantha K.; Gyton, Matthew R.; Twycross, Daniel; Cole, Marcus L.
Abstract : IPrBr: an air stable NHC. A stereoelectronic and catalytic study of IPrBr is reported. Abstract : The air stable NHC IPrBr is reported. A stereoelectronic study of IPrBr and its similarly stable relative IMesBr demonstrates metal complex specific changes in NHC donicity versus the ubiquitous IPr and IMes. Application to a Suzuki coupling and an iridium transfer hydrogenation gives superior outcomes using IPrBr and IMesBr.